Primary greater omental torsion as a cause of acute abdomen—a rare case report - Karanikas, Michael (J Surg Case Rep, 2018)
Greater omental torsion is a rare entity that can cause acute abdominal pain, may mimick other abdominal pathologies, and is difficult to be diagnosed preoperatively. We present a case of a male patient with greater omental torsion mimicking the symptoms of acute appendicitis. A 31-year-old male patient presented with right scrotal pain, initially treated by the urologists, however, 24 h later, he presented right lower quadrant pain, with characteristics of acute appendicitis. After finding in ischemic inflammatory mass on McBurney incision, an exploratory laparotomy was performed, revealing torsion of the greater omentum. Torsion of the greater omentum can be a cause of acute abdomen and could be misdiagnosed with acute appendicitis. Preoperative diagnosis is not easy and resection of the affected tissue is the preferred treatment of choice.